The Influence of Brand Awareness and Brand Trust on Brand Loyalty through Customer Satisfaction as an Intervening Variable (Study on Aqua Drinking Water Consumers in Surabaya) - Adelia, Nabila; Rusdianto, R. Yuniardi (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study was to analyze the effect of brand awareness and brand trust on brand loyalty through customer satisfaction on bottled drinking water for the Aqua brand. This research method is quantitative research with the analysis technique used is path analysis.  The sample used was random sampling with 100 respondents. The result of this study is that brand trust affects customer satisfaction. Meanwhile, brand awareness has no effect on customer satisfaction. Brand awareness affects brand loyalty while brand trust and customer satisfaction have no effect on brand loyalty. Brand trust affects brand loyalty through customer satisfaction, while brand awareness has no effect on brand loyalty through customer satisfaction.